2009
DOI: 10.1371/journal.pone.0004320
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Retinal Ganglion Cells and Their Projections Involved in Central Transmission of Information about Upward and Downward Image Motion

Abstract: The direction of image motion is coded by direction-selective (DS) ganglion cells in the retina. Particularly, the ON DS ganglion cells project their axons specifically to terminal nuclei of the accessory optic system (AOS) responsible for optokinetic reflex (OKR). We recently generated a knock-in mouse in which SPIG1 (SPARC-related protein containing immunoglobulin domains 1)-expressing cells are visualized with GFP, and found that retinal ganglion cells projecting to the medial terminal nucleus (MTN), the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
174
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(193 citation statements)
references
References 78 publications
19
174
0
Order By: Relevance
“…Unlike C6, the cells in this cluster did not respond to decrements in light intensity but only to increases in light intensity (Bias Index ϭ 0.87). The cells of this cluster are predominately the ON directionally selective cells, which play a strong role in controlling image stabilization (Oyster and Barlow 1967;Sun et al 2006;Yonehara et al 2009;Yoshida et al 2001).…”
Section: Delineating the Individual Visual Channelsmentioning
confidence: 99%
“…Unlike C6, the cells in this cluster did not respond to decrements in light intensity but only to increases in light intensity (Bias Index ϭ 0.87). The cells of this cluster are predominately the ON directionally selective cells, which play a strong role in controlling image stabilization (Oyster and Barlow 1967;Sun et al 2006;Yonehara et al 2009;Yoshida et al 2001).…”
Section: Delineating the Individual Visual Channelsmentioning
confidence: 99%
“…Previous studies in rabbits and monkeys showed that a dedicated set of brainstem visual nuclei, termed the "accessory optic system" (AOS) and the retinal ganglion cells (RGCs) that innervate them, are ideally configured to meet these requirements (Oyster et al, 1980;Simpson, 1984;Soodak and Simpson, 1988;Distler and Hoffmann, 2011). A major conclusion of that work and thus the prevailing view for more than three decades was that the primary source of drive to the AOS comes from a subset of directionselective RGCs that respond to increments in light (On-DSGCs) (Yonehara et al, 2009; for review, see Simpson, 1984;Schiller, 2010;Borst and Euler, 2011). Indeed, On-DSGCs respond to slow velocities and have large receptive fields, properties well suited for detecting retinal slip during slow head rotations.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms underlying directional selectivity in retinal ganglion cells (Demb 2007) have been studied intensively in rabbits (e.g., Fried et al 2002Fried et al , 2005Oesch et al 2005) and more recently in mice (Huberman et al 2009;Weng et al 2005;Yoshida et al 2001). Whereas brainstem projections of retinal DS neurons control aspects of eye position (Cavanaugh et al 2012;Dhande et al 2013;Simpson 1984;Yonehara et al 2009), little is known about the function of the projections of retinal DS neurons to thalamocortical circuits. We have previously shown (Swadlow and Weyand 1985) that DS neurons in rabbit LGN do project to the primary visual cortex (V1), that their axons are fast conducting (similar to those of concentrically organized LGN cells), and that LGN DS neurons are much more prevalent in the representation of the upper visual field (dorsal portion of the LGN) than in the representation the visual streak (the region of high receptor and ganglion cell density representing vision along the horizon; Hughes 1971).…”
mentioning
confidence: 99%